Do stages of menopause affect the outcomes of pelvic floor muscle training? - Tosun, Ozge Celiker; Mutlu, Ebru Kaya; Tosun, Gokhan; Ergenoglu, Ahmet Mete; Yeniel, Ahmet Ozgur; Malkoc, Mehtap; Itil, Ismail Mete (Lippincott Williams & Wilkins, 2015)
Objective: The purpose of our study is to determine whether there is a difference in pelvic floor muscle strength attributable to pelvic floor muscle training conducted during different stages of menopause. Methods: One hundred twenty-two women with stress urinary incontinence and mixed urinary incontinence were included in this prospective controlled study. The participants included in this study were separated into three groups according to the Stages of Reproductive Aging Workshop staging system as follows: group 1 (n = 41): stages -3 and -2; group 2 (n = 32): stages +1 and -1; and group 3 (n = 30): stage +2. All three groups were provided an individual home exercise program throughout the 12-week study. Pelvic floor muscle strength before and after the 12-week treatment was measured in all participants (using the PERFECT [power, endurance, number of repetitions, and number of fast (1-s) contractions; every contraction is timed] scheme, perineometry, transabdominal ultrasound, Brink scale, pad test, and stop test). Data were analyzed using analysis of variance. Results: There were no statistically significant differences in pre-exercise training pelvic floor muscle strength parameters among the three groups. After 12 weeks, there were statistically significant increases in PERFECT scheme, Brink scale, perineometry, and ultrasound values. In contrast, there were significant decreases in stop test and 1-hour pad test values observed in the three groups (P = 0.001, dependent t test). In comparison with the other groups, group 1 demonstrated statistically significant improvements in the following postexercise training parameters: power, repetition, speed, Brink vertical displacement, and stop test. The lowest increase was observed in group 2 (P < 0.05). Conclusions: Strength increase can be achieved at all stages of menopause with pelvic floor muscle training, but the rates of increase vary according to the menopausal stage of the participants. Women in the late menopausal transition and early menopause are least responsive to pelvic floor muscle strength training. Further studies in this field are needed.
Keywords: Pelvic floor muscle training; Urinary incontinence symptoms; Pelvic floor muscle strength; Menopause